2019
DOI: 10.1002/acr.23777
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Frequent Emergency Department Utilization Among Persons With Systemic Lupus Erythematosus

Abstract: Objective. In order to identify opportunities to improve outpatient care, we evaluated patients with systemic lupus erythematosus (SLE) who persistently frequent the emergency department (ED).Methods. We conducted a retrospective study of patients with SLE who frequented the ED for ≥3 visits in a calendar year, from 2013 to 2016. Persistent users were those who met criteria for persistent use for at least 2 of the 4 years, and limited users for 1 of the 4 years. Each ED encounter was categorized as SLE-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The variables associated with persistent frequent use found in this study were all reported by previous studies [32,33,35,36], while some studied both occasional frequent use and persistent frequent use [32,33,36]. In those same studies, depending on the studied population, some specific diagnoses were also associated with persistent frequent use, such as COPD diagnosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The variables associated with persistent frequent use found in this study were all reported by previous studies [32,33,35,36], while some studied both occasional frequent use and persistent frequent use [32,33,36]. In those same studies, depending on the studied population, some specific diagnoses were also associated with persistent frequent use, such as COPD diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…In those same studies, depending on the studied population, some specific diagnoses were also associated with persistent frequent use, such as COPD diagnosis. Besides, a few studies mentioned race [32,33] and deprivation indices [32,35,36] as significant, though those latter were not necessarily the same indices as ours. Race was not available in our databases and deprivation indices were not significant in our analyses of persistent frequent use.…”
Section: Discussionmentioning
confidence: 39%
“…In a study using electronic health records, chronic pain was found to be a main cause of emergency room (ER) use among patients with SLE who had frequent ER visits. 31 In addition, long-term opioid use was seen in one out of three patients with SLE who frequented the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Our review from January 2000 to June 2020 identified 9224 abstracts for review; 479 full-text articles were selected for full-text review (Figure 1). Overall, 51 articles met selection criteria and captured the desired outcomes: health care utilization (28 articles), 10, drug utilization (20 articles), 11,24,[28][29][30][32][33][34][35]37,38,41,42,[47][48][49][50][51][52][53] adherence (7 articles), 27,49,51,52,[54][55][56] direct costs (20 articles), 10,11,20,22,24,25,[28][29][30][31][32][33][34][35]40,42,43,[57][58][59] and indire...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among the 39 longitudinal studies included, the length of follow-up range was 6 months to 10 years, with the earliest study periods beginning in 1987. 10,11,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45]47,48,51,53,[56][57][58][59][60]62,68,69 Across all studies, sample sizes varied from fewer than 100 patients up to 340,000 patients, depending on data source, study period, and study objectives. More than 60% of the articles had study populations that were more than 90% female.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%